THE EFFECT OF CIRCUIT LEARNING MODEL ASSISTED BY FLIP CHART MEDIA ON SCIENCE LEARNING OUTCOMES - Dongoran, Jhonas; Faridah, Eva; Surya, Edy; Bukit, Nurdin (JURNAL DARMA AGUNG, 2024)
This study looks into how well flipcharts and the circuit learning model might improve scientific learning results and cooperative attitudes in Indonesian elementary school students. In order to address the widespread problem of low educational quality, the research proposes a novel method of instruction. The underutilization of engaging media in scientific education is the research gap, and the uniqueness is in suggesting the circuit learning model with flipcharts as a possible solution. The study used the independent sample t-test as a quantitative method for assessing hypotheses. The experimental group outperformed the control group in terms of learning outcomes, according to the statistical results. The findings of the t-test (p < 0.05) attest to the effectiveness of the circuit learning model utilizing flipcharts in improving science learning. In particular, there was an increase in student involvement, attention span, and general learning activities when flipchart media was used. These statistical results offer empirical backing for the suggested intervention, indicating that it has the capacity to close the noted research gap and improve students' academic and social learning experiences. The statistically significant findings of this study suggest that teachers should think about implementing the circuit learning model with flipcharts as a successful tactic to enhance scientific teaching outcomes